Analisis Implementasi Permen No 7 Tahun 2019 tentang Pengelolaan Limbah Madis Padat di Rumah Sakit Daerah Kota Tidore Tahun 2023-3024 - Nurlaela, Nurlaela; Pratama M, Nindy (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to determine the process of managing solid medical waste at the Tidore City Regional Hospital and whether it is in accordance with Permenkes No. 7 of 2019. The research method used is a descriptive research method with a qualitative approach. The objects of this study include the head of IPRS, environmental health staff and cleaning services at the Tidore City Regional Hospital. The research instrument uses interview guidelines, stationery and mobile phones. Qualitative data analysis techniques use data reduction, data presentation and drawing conclusions or verification. The results of this study indicate that Permenkes No. 7 of 2019 is not in accordance with the process of transporting and storing solid medical waste. The problems found include the absence of a transport trolley, the transport route still uses the visitor/patient route and the location of the TPS which is close to the service room. The conclusion of this study is that the management of solid medical waste at the Tidore City Regional Hospital can be said to be not in accordance with the management of medical waste according to Permenkes No. 7 of 2019. The advice given to the hospital is to improve the management of solid medical waste, the aim is for the health of the environment and the community around the hospital. Keywords: Analysis of the Implementation of Minister of Health Regulation No. 7 of 2019